2021
DOI: 10.48550/arxiv.2111.01674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minimizing Energy Consumption Leads to the Emergence of Gaits in Legged Robots

Abstract: Legged locomotion is commonly studied and expressed as a discrete set of gait patterns, like walk, trot, gallop, which are usually treated as given and pre-programmed in legged robots for efficient locomotion at different speeds. However, fixing a set of pre-programmed gaits limits the generality of locomotion. Recent animal motor studies show that these conventional gaits are only prevalent in ideal flat terrain conditions while real-world locomotion is unstructured and more like bouts of intermittent steps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Since it is challenging in general to learn a single policy with RL to perform various tasks [48], many prior works focus on learning a single-task policy [16], [17], [49], [50] for legged robots, such as just forward walking [39], [51], [52]. There have been efforts to obtain a multi-task policy, such as walking at different velocities using different gaits, conditioned only on variable commands [46], [53]- [55], which requires more extensive tuning due to the lack of a gait prior. Providing the robot with different reference motions for different skills can be helpful, but requires additional parameterization of the reference motions (e.g., a gait library) [45], [56]- [58], policy distillation [43], or a motion prior [59]- [61].…”
Section: Related Workmentioning
confidence: 99%
“…Since it is challenging in general to learn a single policy with RL to perform various tasks [48], many prior works focus on learning a single-task policy [16], [17], [49], [50] for legged robots, such as just forward walking [39], [51], [52]. There have been efforts to obtain a multi-task policy, such as walking at different velocities using different gaits, conditioned only on variable commands [46], [53]- [55], which requires more extensive tuning due to the lack of a gait prior. Providing the robot with different reference motions for different skills can be helpful, but requires additional parameterization of the reference motions (e.g., a gait library) [45], [56]- [58], policy distillation [43], or a motion prior [59]- [61].…”
Section: Related Workmentioning
confidence: 99%
“…The mechanical design of the ANYmal robot is thought to limit it from running at higher speeds. [13,23] investigated the capability of model-free controllers to efficiently traverse diverse terrains on the Unitree A1, a small robot with similar size, actuation, and cost to the Mini Cheetah. Although the A1's built-in MPC controller has a maximum running speed of 3.3 m/s, these learning-based works only demonstrated the robot running up to maximum speed 1.8 m/s.…”
Section: Ablation Studiesmentioning
confidence: 99%
“…While a higher planning ability may contribute to a more successful predator and therefore a higher gain in energy, it is very energetically costly to run these systems. Additionally, prior work in robotics has shown that under different scenarios, systems will find different optimal policies to minimize energy consumption [12].…”
Section: Reproducing Biologymentioning
confidence: 99%